Effects of Routine Health Care Combined with Oral Vitamin D on Linear Growth in 5-Year-Old Children. (21st June 2022) - Zeng, Qingwen; Liu, Yangyang
Abstract : Objective . The aim is to evaluate the effects of routine health care combined with oral vitamin D on linear growth in 5-year-old children. Materials and Methods . The 5-year-old children who received routine health care in Shiyan Maternal and Child Health Care Hospital from January 2019 to January 2021 were retrospectively analyzed. They were divided into the supplement group and the non-supplement group according to whether or not they received oral vitamin D, and reasons for not taking oral vitamin D and its influence on children's linear growth were analyzed. Results . A total of 368 children were enrolled, including 228 children in the supplement group, accounting for 61.96%. The analysis of the influencing factors of vitamin D supplementation showed that the proportion of children with well-educated parents and living in cities and towns was higher (all P < 0.05 ). Comparing the general situation of children in the two groups, it was found that the height, weight, and head circumference of children in the supplement group were notably higher than those in the non-supplement group (all P < 0.05 ). At age 4 and 5, the height of the supplement group was significantly higher than that of the non-supplement group (all P < 0.001 ). Linear analysis showed that the relationship between height and age in the supplement group was Y (height, cm) = 10.07 × X (age, years) + 61.18, while that in the non-supplement group was Y (height, cm) = 8.296 × X (age, years) + 62.81, with significant difference (all P < 0.05 ). Serum 25-hydroxyvitamin D concentration in the supplement group was significantly higher than that in the non-supplement group, and the proportion of children ≥75 nmol/L was evidently higher than that in the supplement group (all P < 0.05 ). In addition, the incidence of vitamin D-related hypercalcemia in the supplement group was significantly higher than that in the non-supplement group (all P < 0.05 ). Conclusion . There are still more children without vitamin D supplement, which is closely related to their parents' education background and place of residence. Additionally, vitamin D supplementation can promote growth and improve 25-hydroxyvitamin D levels in children, but with the risk of related complications.